Prediticing academic procastinantion in students: Perfectionism, general self-efficacy, and sociodemographic factors - Wardani, Ria; Adelina, Ira; Santoso, Juliati Ardhi (Indigenous, 2021)
Abstract. Procrastination is frequently found in around 30% to 60% of college students. Research that examines academic procrastination is associated with adaptive-maladaptive perfectionism, general self-efficacy, and sociodemographic factors, expected to gain a comprehensive understanding of procrastination so that anticipatory and countermeasures can be implemented. The target population of this study was male and female college students from state and private universities. The questionnaire was distributed physically and digitally (google-form) to 208 participants using the snowball sampling technique. Theresearch instrument consisted of the Academic Procrastination Scale (APS), The Frost Multidimensional Perfectionism Scale (FMPS), General Self-Efficacy (GSE), and questions on sociodemographic factors. All research instruments have been tested and met the criteria of validity and reliability. After the data cleaning and coding process, the data were assessed using multiple regressions dan hierarchical regression. The data analysis revealed that perfectionism and self-efficacy were generally predictors of procrastination. Similarly, from the results of model testing, all sociodemographic factors simultaneously affected procrastination, but gender was in line with influencing procrastination. Research findings show that procrastination was more motivated by many anxieties due to excessive attention to mistakes and doubts in acting. This research has limitations, namely the origin of the participating universities, primarily private universities rather than state universities. As a result, the level of variability of data sources tends to below. However, this study results can be followed up to address the issue of academic procrastination.Keywords: academic procrastination; adaptive and maladaptive perfectionism; general self-efficacy; sociodemographic